Социология: учебник для вузов - Волков Ю. Г. Юрий Григорьевич; Добреньков В. И. Владимир Иванович; Нечипуренко В. Н. Виктор Николаевич; Попов А. В. Александр Васильевич (Disciplinae)
Исключено из фонда НТБ ТПУ